Effect of craniofacial measures on the cephalic index of Japanese adult female students - Hossain, M.G.; Sabiruzzaman, M.; Islam, S.; Ohtsuki, F.; Lestrel, P.E. (Anthropological Soc Nippon, 2010)
This study was designed to identify possible craniofacial measurements that have an influence on the cephalic index (CI) of Japanese adult females The total sample used in the current study consisted of 832 healthy Japanese adults. The subjects were all of Japanese birth and ancestry. The age range of the subjects was between 18-25 years. Eight craniofacial measurements were taken head length, head breadth, head height, head circumference, minimum frontal breadth, bizygomatic breadth, bigonial breadth, and morphological face height. In addition, stature and body weight were also measured All measurements were taken by one observer from 1998 to 2001. The CI was calculated from head length and head breadth Using multiple regression analysis, a variance inflation factor (VIF) demonstrated that there was no evidence of a multicollinearity problem among the variables when CI was considered as a response variable The coefficients of the regression line demonstrated that there was a significant positive relationship between the CI and minimum frontal breadth (P < 0.01), bizygomatic breadth (P < 0.01) and head height (P < 0.05), while a negative relationship was round between the CI and morphological facial height (P < 0.05) and head circumference (P < 0.01). Moreover, the coefficient and odds ratio of the logistic regression showed that minimum frontal breadth (P < 0.05), bizygomatic breadth (P < 0.01), and head height (P < 0.05) were more likely in the round-headed group, while morphological facial height (P < 0.05), head circumference (P < 0.01), and stature (P < 0.05) were less likely in the round-headed group Stepwise regression analysis showed that with respect to the CI, the best predictor variables were bizygomatie breadth, head circumference, minimum frontal breadth, morphological facial height, head height, and stature These results suggest that most of the craniofacial variables measured appear to influence the CI of Japanese adult female students.